REJUVENATING THE GROUNDWATER TAX STRATEGY IN GARUT REGENCY - Muslim Al Kautsar; Acep Abdul Basit; Abdullah Ramdhani; Hanifah Fauiziah (JAF (Journal of Accounting and Finance), 2021)
This research purpose to analyze the strategic and technical to encourage the potential of Regional Original Revenue (PAD) from the Groundwater Tax sector owned by Garut Regency. In this research used the descriptive method of research and qualitative approach to obtain the illustration of groundwater tax potential in Garut Regency. The primary and secondary data obtained by depth-interview technique to The Regional Revenue Office of Garut Regency. The data analysis using the formula on the growth, contribution and potential. Besides that, in this research use SWOT analysis to identify internal and external factors that influence the achievement of organizational goals based on strengths, weakness, opportunity, and threatness. The result of this research based on the growth measurement obtained the average of the ground water tax reached -13.65% while the contribution of ground water tax to the regional tax was 0.83%. Thus, to repair this condition based on the SWOT analysis the government of Garut Regency needs to conduct the intensification and extensification to increase groundwater tax revenues in Garut Regency as rejuvenating the policy of groundwater tax strategy in Garut Regency.